2021
DOI: 10.2147/rmhp.s299169
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prior Digestive System Disease on In-Hospital Gastrointestinal Bleeding in Patients with Acute Myocardial Infarction

Abstract: Objective: Patients presenting with acute myocardial infarction (AMI) with prior digestive system disease are more likely to suffer from gastrointestinal (GI) bleeding than those without these diseases. However, few articles reported how the different conditions of the digestive tract produced different risks of GI bleeding. Methods: A single-center study on 7464 patients admitted for AMI from December 2010 to June 2019 in the Beijing Chaoyang Heart Center was retrospectively examined. Patients with major GI b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Second, all the existing studies only investigated the safety of PPI use which was started after AMI had been established. Third, the benefit of using PPI for stress ulcer prophylaxis in critically ill settings may also apply to AMI patients ( 32 , 33 ), as stress ulcer and related gastrointestinal bleeding are not rare in AMI patients ( 34 ) and early use of PPI may benefit AMI patients by decreasing gastrointestinal bleeding ( 35 ). Fourth, both the trials and observational studies revealed that the use of PPI significantly reduced the risks of gastrointestinal bleeding when receiving dual antiplatelet therapy which was indicated for AMI ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, all the existing studies only investigated the safety of PPI use which was started after AMI had been established. Third, the benefit of using PPI for stress ulcer prophylaxis in critically ill settings may also apply to AMI patients ( 32 , 33 ), as stress ulcer and related gastrointestinal bleeding are not rare in AMI patients ( 34 ) and early use of PPI may benefit AMI patients by decreasing gastrointestinal bleeding ( 35 ). Fourth, both the trials and observational studies revealed that the use of PPI significantly reduced the risks of gastrointestinal bleeding when receiving dual antiplatelet therapy which was indicated for AMI ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…AIA is a disparate clinical syndrome expressed by adverse respiratory reactions to ASA and distinct NSAIDs [46]. ASA cause Intracerebral Hemorrhage owing to prolonged bleeding time [47]; Fatal airway obstruction in asthmatic patients/bronchospasm; Hypersensitivity [48,49]; hepatotoxicity and cardiovascular collapse; Blood and the lymphatic system disorders [50]; Renal and urinary disorders [51]; Skin and subcutaneous tissue disorders [52]; GI disorders owing to ASA inhibits, COX, which is accountable for generation of prostaglandins which protect GI mucosal layers [53]; Ear and labyrinth disorders [54].…”
Section: Adrmentioning
confidence: 99%